Distance of interaction: a phenomenological analysis of elastic scattering data induced by light projectiles - Valdir Guimarães; Pierre Camilo Nistal; Sunday D. Olorunfunmi; Sunday D. Olorunfunmi; Roberto Linares; Jesus Lubian (Frontiers in Physics)
IntroductionA phenomenological analysis, based on distances, has been performed for elastic scattering data induced by tightly bound (11B, 12C, and 16O), weakly bound (6Li, 7Li, 7Be, and 9Be), and exotic (6He, 8B, 11Be, and 15C) nuclei on light (27Al), medium (58Ni and 120Sn), and heavy mass (208Pb) targets, respectively, at energies close to the Coulomb barrier.MethodsThe cross-section data on the angular distributions have been converted as a function of the distance of the closest approach.ResultsFrom a fitting analysis, critical interaction and strong absorption distances were extracted from the data.DiscussionCorrelation was observed with the projectile cluster configuration for the data on the target 208Pb.